An In Situ Gelling Drug Delivery System for Improved Recovery after Spinal Cord Injury. Issue 12 (26th April 2016) - Liu, Dongfei; Jiang, Tao; Cai, Weihua; Chen, Jian; Zhang, Hongbo; Hietala, Sami; Santos, Hélder A.; Yin, Guoyong; Fan, Jin
Abstract : Therapeutic strategies for the spinal cord injury (SCI) are limited by the current available drug delivery techniques. Here, an in situ gelling drug delivery system (DDS), composed of a Poloxamer‐407, a 188 mixture‐based thermoresponsive hydrogel matrix and, an incorporated therapeutic compound (monosialoganglioside, GM1), is developed for SCI therapy. A low‐thoracic hemisection in rats is used as SCI model to evaluate therapeutic efficiency. The GM1‐incorporating Poloxamer‐407 and 188 polymer solution is converted to a hydrogel (GM1‐hydrogel) upon instillation to the injured spinal cord, due to the increased temperature. At body temperature, the thermoresponsive hydrogel prolongs the release of GM1 for about 1 month, due to the superposition of dissolution and swelling (anomalous transport) of the hydrogel matrix. The sustained release of the GM1‐hydrogel enables the prolonged residence time of GM1 at the injured spinal cord, decreases the frequency of administration and, consequently, may improve patient compliance. After SCI, the administration of GM1‐hydrogel to the lesion site inhibits the apoptotic cell death and glial scar formation, enhances the neuron regeneration, provides neuroprotection to the injured spinal cord, and improves the locomotor recovery. Overall, this study opens future perspectives for the treatment of SCI with a prolonged drug release DDS. Abstract : An in situ gelling drug delivery system is developed for spinal cord injury therapy . The administration of drug‐incorporated hydrogel inhibits the apoptotic cell death and glial scar formation, enhances the neuron regeneration, provides neuroprotection to the injured spinal cord, and ultimately improves the locomotor recovery in rats.